Intergenerational Patterns in Offending: Lessons from the Rochester Intergenerational Study—ASC Division of Developmental and Life Course Criminology David P. Farrington Lecture, 2019 - Thornberry, Terence P. (Journal of developmental and life-course criminology, 2020)
In recent years, criminology has seen an increase in the number of three-generation, prospective studies of offending. The most fundamental question posed by these studies is whether, and to what extent, parental involvement in adolescent delinquency increases the risk of offending by their offspring. There are several important substantive and methodological challenges that need to be confronted in assessing the intergenerational effect, including the examination of moderating influences that can change the level of intergenerational continuity and methodological issues as such definitional elasticity—the impact on the level of intergenerational continuity that is likely to be observed based on (a) how offending is defined and (b) how the inherent heterogeneity in offending is taken into accounted., To examine these issues, I use data from the Rochester Intergenerational Study (RIGS), an extension of the original Rochester Youth Development Study (RYDS). RYDS began data collection in 1988 with a sample of 1000 adolescents and one of their parents. The intergenerational study began in 1999 by adding a third generation member―the oldest biological child of the initial adolescent participants―and following them over time with 19 annual assessments., Overall, there is a significant positive association between a parent’s involvement in adolescent delinquency and the likelihood that their offspring will also be involved in delinquency. That overall relationship, however, masks substantial internal variability. The significance and size of the intergenerational effect vary by such factors as the level of ongoing contact between fathers and their children and the child’s gender. It is also influenced by methodological considerations such as definitional elasticity. Under some definitions of delinquent behavior, a robust relationship between the parent’s delinquency and the child’s is observed, while under other definitions, there is no significant relationship., There is, as of now, no clear and consistent answer to the question of whether or not children follow in the footsteps of their parents with respect to delinquency. The field of intergenerational study, which is still relatively new, needs to confront more directly and systematically how both substantive and methodological issues that can influence estimates of the intergenerational effect.